Effects of Ferulago angulata Extract Against Oxidative Stress Induced by 6-hydroxydopamine in Rats - Fatemeh Sharifi; Maryam Rafieirad; H Sazegar (Institue of Medicinal Plants, ACECR, 2015)
Background: Parkinsonchr('39')s disease is one of the prevalent degenerative diseases of the neural system. Oxidative stress, which has been recognized as the most important factor of Parkinsonchr('39')s disease, plays a main role in the death of neurons in this disease. Antioxidants have a proved role in the prevention of oxidative stress. Objective: Considering the presence of evidence regarding antioxidant property of Ferulago angulata, effect of oral administration of hydroalcoholic extract of this plant was investigated on parameters of the oxidative damage caused by Parkinsonchr('39')s disease in adult rats. Methods: In this research, 40 Wistar rats with the average weight of 200 to 250 g were randomly assigned to 5 groups, each with 8 rats. Also, to develop Parkinsonchr('39')s disease animal model, 2 µl of 6-hydroxydopamine drug was injected into medial forebrain bundle on the left side of the animals and the treatment groups received Ferulago angulata extract with doses of 400, 200, and 100 mg/kg for 2 weeks as gavage. Then, the brain of the animals was isolated and parameters of Malondialdehyde and Thiol were measured. Results: Results showed that Parkinsonchr('39')s disease induced significantly increased brain peroxidation lipid, which is one of the factors of oxidative stress, and reduced Thiol level (p<0.001). Further, treatment of Parkinsonchr('39')s disease with Ferulago angulata extract significantly decreased peroxidation lipid in striatum and hippocampus and increased Thiol level (p<0.001). Conclusion: oral administration of hydroalcoholic extract of Ferulago angulata probably reduces oxidative damage and also reduces Malondialdehyde and increases Thiol in the treated groups due to its strong antioxidant property.